2013
DOI: 10.1161/circulationaha.112.000882
|View full text |Cite
|
Sign up to set email alerts
|

MiR-378 Controls Cardiac Hypertrophy by Combined Repression of Mitogen-Activated Protein Kinase Pathway Factors

Abstract: Background— Several microRNAs (miRs) have been shown to regulate gene expression in the heart, and dysregulation of their expression has been linked to cardiac disease. miR-378 is strongly expressed in the mammalian heart but so far has been studied predominantly in cancer, in which it regulates cell survival and tumor growth. Methods and Results— Here, we report tight control of cardiomyocyte hypertrophy through miR-378. In isolated primary cardiomyocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(172 citation statements)
references
References 43 publications
7
160
1
4
Order By: Relevance
“…This result is in line with a growing body of evidence demonstrating that microRNAs play a role in modulating specific receptor pathways in cardiomyocytes. 24,25 For example miR-1, which together with miR-133 is one of the most highly expressed microRNAs in the heart and is transcribed from the same bicistronic unit as miR-133, was found by us and others to regulate the insulin-like growth factor 1/insulin-like growth factor 1 receptor signal transduction pathway, 25,34 a key regulator of cardiac muscle trophism and function. Recent studies have demonstrated a role of βAR signaling in controlling microRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in line with a growing body of evidence demonstrating that microRNAs play a role in modulating specific receptor pathways in cardiomyocytes. 24,25 For example miR-1, which together with miR-133 is one of the most highly expressed microRNAs in the heart and is transcribed from the same bicistronic unit as miR-133, was found by us and others to regulate the insulin-like growth factor 1/insulin-like growth factor 1 receptor signal transduction pathway, 25,34 a key regulator of cardiac muscle trophism and function. Recent studies have demonstrated a role of βAR signaling in controlling microRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Primary neonatal cardiomyocytes were isolated from 1-day-old Sprague-Dawley rats as described previously (Ganesan et al, 2013). Isolated cardiomyocytes and 293T cells (American Type Culture Collection, Manassas, VA, USA) were cultured in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum, 1 mM glutamine, 100 U/mL penicillin, and 100 mg/mL streptomycin.…”
Section: Cell Culture Transfection and Cell Surface Area Measurementmentioning
confidence: 99%
“…The cell surface area of α-actin-stained cells or unstained cells was measured as described previously (Ganesan et al, 2013). A total of 100-200 cardiomyocytes in 20-50 fields were examined in each experiment.…”
Section: Cell Culture Transfection and Cell Surface Area Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the heart, miR-378 targets growth factor receptor-bound protein 2 (GRB2), insulin-like growth factor 1 receptor (IGF1R), kinase suppressor of ras 1 (KSR1), as well as MAPK1. MiR-378 serves as an endogenous negative regulator of cardiac hypertrophy through the repression of the RAS signaling pathway (9). More information on the miRNA profile associated with cardiac disease has been emerging (10).…”
Section: Mirnasmentioning
confidence: 99%